Clostridioides difficile Whole-genome Sequencing Differentiates Relapse With the Same Strain From Reinfection With a New Strain. (17th February 2020) - Cho, Janice; Cunningham, Scott; Pu, Meng; Lennon, Ryan J; Dens Higano, Jennifer; Jeraldo, Patricio; Sampathkumar, Priya; Shannon, Samantha; Kashyap, Purna C; Patel, Robin
Abstract: Background: Current approaches in tracking Clostridioides difficile infection (CDI) and individualizing patient management are incompletely defined. Methods: We recruited 468 subjects with CDI at Mayo Clinic Rochester between May and December 2016 and performed whole-genome sequencing (WGS) on C. difficile isolates from 397. WGS was also performed on isolates from a subset of the subjects at the time of a recurrence of infection. The sequence data were analyzed by determining core genome multilocus sequence type (cgMLST), with isolates grouped by allelic differences and the predicted ribotype. Results: There were no correlations between C. difficile isolates based either on cgMLST or ribotype groupings and CDI outcome. An epidemiologic assessment of hospitalized subjects harboring C. difficile isolates with ≤2 allelic differences, based on standard infection prevention and control assessment, revealed no evidence of person-to-person transmission. Interestingly, community-acquired CDI subjects in 40% of groups with ≤2 allelic differences resided within the same zip code. Among 18 subjects clinically classified as having recurrent CDI, WGS revealed 14 with initial and subsequent isolates differing by ≤2 allelic differences, suggesting a relapse of infection with the same initial strain, and 4 with isolates differing by >50 allelic differences, suggesting reinfection. Among the 5 subjects classified as having a reinfection based on the timing of recurrence, 3 had isolates with ≤2 allelic differences between them, suggesting a relapse, and 2 had isolates differing by >50 allelic differences, suggesting reinfection. Conclusions: Our findings point to potential transmission of C. difficile in the community. WGS better differentiates relapse from reinfection than do definitions based on the timing of recurrence. Abstract : Whole-genome sequencing of Clostridioides difficile can differentiate a relapse of infection with the same strain from an infection with a new strain, which may be helpful in individualizing treatment.